Awareness of Employees about their Actual Compensation - Rinki Mishra (AG Volumes, 2022)
Salary is the most common kind of pay that comes to mind. The HRM perspective on pay, however, takes into account a far broader set of advantages. In addition to a salary, an employee could be eligible for health insurance and other benefits as part of their remuneration package. Since salary and perks have such a significant impact on an employee’s performance and motivation, they are also key factors in ensuring that an employee enjoys working for their company. Because of this, it is crucial for an HR division to provide competitive compensation and benefits packages to its employees. The company’s dedication to its employees and appreciation for their efforts would be readily apparent if this is done. When everything is said and done, an organization’s employees are its greatest asset. Employers have a responsibility to ensure that workers are aware of the full value of their pay package, which includes more than just their base income, throughout the recruiting process as well as during the whole of the employee experience. Awareness and appreciation are essential components of successful recruiting and retention strategies.